Guerra e construção do estado no Brasil imperial - Pereira, Matheus Dalbosco (2019)
The research aims to analyze the relationship between wars and state capacity, in order to answer the following question: “What were the impacts of wars, which occurred in the imperial period, on the capabilities of the Brazilian state? To this end, the paper sought to test Centeno's (2002) hypotheses: (1) the extractive capacity was not expanded because the wars were financed with international loans; and (2) the wars in which Brazil participated were of the limited type and thus had minor impacts on state capabilities (limited wars produced limited states). The following wars were analyzed: The Cisplatin War (1825-1828), the War against Rosas (1852), and the Paraguayan War (1864-1870), defined as rivalry and limited war; opportunity and limited war; and total war, respectively. The interval is justified because it is the most bellicose phase in Brazilian history, allowing a more similar analysis of the bellicose model developed by Tilly (1996), and the different types of wars choosed allows the analysis of the second hypothesis. This is a single case study with multiple comparisons within the case and adopts the theoretical-methodological tool of path dependence. Finally, the study partially confirmed the first hypothesis, since the wars did not expand the state's extractive capacity and the high war costs contributed significantly to the country's debt increase. It is noteworthy, however, that the problem is not the use of international loans, but the inability of the Brazilian state to extract resources from its elites. The second hypothesis, that limited wars cause reduced impacts on state capacities, was not confirmed, because the different types of wars produced similar results.